Housing Affordability in the Visegrád Countries - Ardielli, Eva; Kovács, Robert; Slavata, David (Publishing House of Wroclaw University of Economics and Business, 2024)
Housing has always been, is and most likely will be a very sought-after and important good from the point of view of members of society. It has the potential to support households in fulfilling a whole range of their needs, and has many unique features, among which cost is a very important one. This means that a household must have sufficient financial resources to be able to purchase property. Housing affordability shows whether a typical family earns enough income to qualify for a mortgage loan on a typical home at the national and regional levels based on the most recent price and income data (Housing Affordability Index). It informs how easily a household can buy its own home based on its own income. The V4 countries have undergone an enormous economic transformation in the last 30 years, which also concerned the housing market. Thus this chapter aimed to compare Czech, Polish and Hungarian regions based on selected housing indicators and assess the level of housing affordability using the calculated Housing Affordability Index (SAI). The research was to determine whether similar trends were observed across the regions of the three Visegrád countries.
Ardielli, E., Kovács, R., Maciejasz, M., & Slavata, D. (2024). Housing Affordability in the Visegrád Countries. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 163-181). Publishing House of Wroclaw University of Economics and Business.
Keywords: housing affordability; housing affordability index; Visegrad Countries